A survey of tuberculosis infection control practices at the NIH/NIAID/DAIDS-supported clinical trial sites in low and middle income countries. Issue 1 (December 2016) - Godfrey, Catherine; Tauscher, Gail; Hunsberger, Sally; Austin, Melissa; Scott, Lesley; Schouten, Jeffrey; Luetkemeyer, Anne; Benson, Constance; Coombs, Robert; Swindells, Susan
Abstract Background Health care associated transmission ofMycobacterium tuberculosis (TB) is well described. A previous survey of infection control (IC) practices at clinical research sites in low and middle income countries (LMIC) funded by the National Institute of Allergy and Infectious Diseases (NIAID) conducting HIV research identified issues with respiratory IC practices. A guideline for TB IC based on international recommendations was developed and promulgated. This paper reports on adherence to the guideline at sites conducting or planning to conduct TB studies with the intention of supporting improvement. Methods A survey was developed that assessed IC activities in three domains: facility level measures, administrative control measures and environmental measures. An external site monitor visited each site in 2013–2014, to complete the audit. A central review committee evaluated the site-level survey and results were tabulated. Fisher's exact test was performed to determine whether there were significant differences in practices at sites that had IC officers versus sites that did not have IC officers. Significance was assessed atp </=.05 Results Seven of thirty-three sites surveyed (22 %) had all the evaluated tuberculosis IC (TB IC) elements in place. Sixty-one percent of sites had an IC officer tasked with developing and maintaining TB IC standard operating procedures. Twenty-two (71 %) sites promptly identified and segregated individuals with TB symptoms. Thirty (93 %) sites had a separate waiting area for patients, and 26 (81 %) collected sputum within a specific well-ventilated area that was separate from the general waiting area. Sites with an IC officer were more likely to have standard operating procedures covering TB IC practices (p = 0.02) and monitor those policies (p = 0.02) and perform regular surveillance of healthcare workers (p = 0.02). The presence of an IC officer had a positive impact on performance in most of the TB IC domains surveyed including having adequate ventilation (p = 0.02) and a separate area for sputum collection (p = 0.02) Conclusions Specific and targeted support of TB IC activities in the clinical research environment is needed and is likely to have a positive and sustained impact on preventing the transmission of TB to both health care workers and vulnerable HIV-infected research participants.